Fully Integrated Design of a Stretchable Solid‐State Lithium‐Ion Full Battery. Issue 43 (6th September 2019) - Chen, Xi; Huang, Haijian; Pan, Long; Liu, Tian; Niederberger, Markus
Abstract: A solid‐state lithium‐ion battery, in which all components (current collector, anode and cathode, electrolyte, and packaging) are stretchable, is introduced, giving rise to a battery design with mechanical properties that are compliant with flexible electronic devices and elastic wearable systems. By depositing Ag microflakes as a conductive layer on a stretchable carbon–polymer composite, a current collector with a low sheet resistance of ≈2.7 Ω □ −1 at 100% strain is obtained. Stretchable electrodes are fabricated by integrating active materials with the elastic current collector. A polyacrylamide–"water‐in‐salt" electrolyte is developed, offering high ionic conductivity of 10 −3 to 10 −2 S cm −1 at room temperature and outstanding stretchability up to ≈300% of its original length. Finally, all these components are assembled into a solid‐state lithium‐ion full cell in thin‐film configuration. Thanks to the deformable individual components, the full cell functions when stretched, bent, or even twisted. For example, after stretching the battery to 50%, a reversible capacity of 28 mAh g −1 and an average energy density of 20 Wh kg −1 can still be obtained after 50 cycles at 120 mA g −1, confirming the functionality of the battery under extreme mechanical stress. Abstract : A solid‐state lithium‐ion battery, in which all components (current collector, anode and cathode, electrolyte, and packaging) are stretchable, is designed and fabricated. The thin‐film full cell can be stretched up to 50% of its original length during the charge and discharge process.